PENGGUNAAN MEDIA MONOPOLI KEBERAGAMAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA PEMBELAJARAN IPS KELAS V DI SDN 08 TILAMUTA KABUPATEN BOALEMO, GORONTALO - Saipi, Andre; Pomalingo, Pomalingo; Nurainun, Nurainun (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to improve student learning outcomes in Social Sciences (IPS) learning in class V of SDN 08 Tilamuta, Boalemo Regency. The method used is Classroom Action Research (CAR) with data collection techniques through interviews, observations, tests, and documentation. The subjects of the study were fifth-grade students at the school. The results showed that in cycle I, only 7 students achieved the Minimum Completion Criteria (KKM) with a percentage of 41%. However, in cycle II, there was a significant increase, where 15 students managed to achieve KKM with a percentage of 88%. The conclusion of this study shows that the implementation of the Monopoly of Diversity media can effectively improve the learning outcomes of fifth-grade students at SDN 08 Tilamuta, Boalemo Regency. This study suggests the use of innovative learning media to improve student motivation and learning outcomes in the future.